Sertraline Delivered in Phosphatidylserine Liposomes Is Effective in an Experimental Model of Visceral Leishmaniasis - Romanelli, Maiara Maria; Costa-Silva, Thais Alves da; Cunha-Junior, Edezio; Dias Ferreira, Daiane; Guerra, Juliana M.; Galisteo, Andres Jimenez; Pinto, Erika Gracielle; Barbosa, Leandro R. S.; Torres-Santos, Eduardo Caio; Tempone, Andre Gustavo (Frontiers in Cellular and Infection Microbiology, 2019)
Liposomes containing phosphatidylserine (PS) has been used for the delivery of drugs into the intramacrophage milieu. Leishmania (L.) infantum parasites live inside macrophages and cause a fatal and neglected viscerotropic disease, with a toxic treatment. Sertraline was studied as a free formulation (SERT) and also entrapped into phosphatidylserine liposomes (LP-SERT) against intracellular amastigotes and in a murine model of visceral leishmaniasis. LP-SERT showed a potent activity against intracellular amastigotes with an EC50 value of 2.5 μM. The in vivo efficacy of SERT demonstrated a therapeutic failure. However, when entrapped into negatively charged liposomes (−58 mV) of 125 nm, it significantly reduced the parasite burden in the mice liver by 89% at 1 mg/kg, reducing the serum levels of the cytokine IL-6 and upregulating the levels of the chemokine MCP-1. Histopathological studies demonstrated the presence of an inflammatory infiltrate with the development of granulomas in the liver, suggesting the resolution of the infection in the treated group. Delivery studies showed fluorescent-labeled LP-SERT in the liver and spleen of mice even after 48 h of administration. This study demonstrates the efficacy of PS liposomes containing sertraline in experimental VL. Considering the urgent need for VL treatments, the repurposing approach of SERT could be a promising alternative.